The Relationship between Variations In Teaching Skills of Tutors and Learning Motivation of Learning Package C Citizens In SPNF SKB Kota Pariaman - Dilia, Reschia Nofour; Irmawita, Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The aim of this research is to find out the picture and also the relationship between the skills of applying variations in tutor teaching and the learning motivation of residents studying Package C at SPNF SKB Kota Pariaman. This research uses a correlational quantitative approach. The population of this research is all students registered in the package C pursuit program at SPNF SKB Kota Pariaman for the 2023/2024 academic year, namely 72 people. The sampling technique in this research was carried out using cluster random sampling, so the total sample that the researchers took was 50 residents studying package C at SPNF Kota Pariaman. The data collection technique uses a questionnaire format and a list of statements as a data collection tool, the data analysis technique uses percentages to find correlations using the product moment formula. The results of this research are: 1.) Skills in applying variations in tutor teaching to students studying at SPNF SKB Kota Pariaman are classified as less than optimal, 2.) Motivation of students studying Package C at SPNF SKB Kota Pariaman is classified as less than optimal and 3.) There is a significant relationship between skills in applying variations in tutor teaching with learning motivation for residents studying Package C at SPNF SKB Kota Pariaman.Keywords: Variasi Mengajar, Motivasi Belajar, SKB.